FLAT-FACADE ELEMENTS IN CONTEMPORARY HOUSING - A. I. Belousov (Наука и техника)
The solution for one of the most acute problems in the Byelorussian architecture is presented in the paper. Among flat-facade elements in the block of flats a preference is given to a unary pier veranda at the kitchen. Building of unary pier balconies, tape balconies and verandas, French balconies is possible under certain conditions. Loggias and terraces are inexpedient.